PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (STUDI PADA YAYASAN PERGURUAN HAMONG PUTERA DI SLEMAN) - Kukuh Briliarto (Faculty of Economics and Business | Universitas Diponegoro, 2020)
This research was conducted at the Hamong Putera Educational Foundation. The purpose of this study was to analyze the direct effect of compensation and job satisfaction on teacher performance in the Hamong Putera Foundation and the indirect effect of compensation and job satisfaction on teacher performance through organizational commitment. Data was collected from March 2020 to April 2020, using the census method with 46 respondents. Primary data collection is done by using a questionnaire method compiled with a Likert scale and then calculated using the path analysis data processing method. The results of this study indicate that 1) There is a direct effect of compensation on teacher performance, 2) There is a direct effect of job satisfaction on teacher performance, 3) There is an indirect effect of compensation on teacher performance through organizational commitment as an intervening variable, 4) There is an indirect effect of satisfaction work on teacher performance through organizational commitment as an intervening variable..